Penatalaksanaan jaringan gingiva dalam penggunaan retraction cord - Pratama Sarwono, Aditya; Fitriyasari, Rahmah (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Introduction: Tooth loss affects a person's appearance and health, impacting their quality of life. Teeth play an essential role in chewing and aesthetics, particularly the anterior teeth. Dental trauma such as fractures can affect appearance and psychology, reducing self-confidence. Currently, aesthetics is a top priority in dental care. Tooth loss leads to complex oral problems, thus missing teeth need to be replaced with dentures. Methods: This study explores the use of various gingival retraction techniques before impression taking in prosthodontic treatment. The methods analyzed include mechanical, chemical, and surgical techniques, with a focus on retraction using retraction cords soaked in hemostatic agents to ensure accurate and blood-free gingival margins before impression taking. Discussion: Accurate impressions depend on proper tooth preparation and healthy soft tissue conditions. Effective gingival retraction is crucial for obtaining good impressions, especially at the cervical and gingival margins. Mechanical methods using retraction cords are commonly used due to their effectiveness, speed, simplicity, and affordability. However, chemical methods may pose risks to the gingiva, while surgical methods are more complex. Conclusion: Accurate impressions for fixed dentures require healthy soft tissues without periodontal disease. Gingival retraction before impression taking is essential for achieving accurate impressions, ensuring that the cervical margins are well defined. Retraction methods include mechanical, chemical, and surgical approaches, with mechanical methods being the common choice due to their effectiveness and simplicity.